Augmented activity of the forearm extensor muscles induced by vibratory stimulation of the palm of the hand in individuals with subacute post-stroke hemiplegia. (12th May 2022) - Kimura, Nodoka; Sato, Mamiko; Kobayashi, Yasutaka; Naito, Eiichi
ABSTRACT: Primary Objective: To examine whether vibration to the palm of the hand induces motor activity in the forearm muscles of individuals with post-stroke and healthy young adults. We hypothesized that the vibration would induce antagonistic muscle activities via the motor cortex. Research Design: Observational study using the between- and within-subjects mixed design. Methods and Procedures: Vibratory stimulation was applied to the palm of the paretic and non-paretic hands in seven post-stroke hemiplegia, and of the right hand in 22 healthy young adults in the eyes-closed and eyes-open conditions. Surface electromyography (sEMG) was recorded from the forearm extensors and flexors and the sEMG amplitudes were analyzed. Main Outcomes and Results: The extensor activities were significantly larger than that of the flexors in all hands. Especially, the extensor activities were augmented when the eyes were open in the paretic and non-paretic hands. Moreover, there was greater muscle activity in the non-paretic hand compared with the paretic hand. Conclusions: These novel findings revealed that vibration to the palm augmented the activity of the antagonistic forearm extensors, especially in the paretic hand, which was induced via top-down cortical modulation. Thus, it can be utilized to improve the impaired forearm extensors in post-stroke rehabilitation.